An integrated approach to system dynamics and data envelopment analysis for determining efficient policies and forecasting travel demand in an urban transport system. Issue 2 (7th February 2022) - Norouzian-Maleki, Pegah; Izadbakhsh, Hamidreza; Saberi, Morteza; Hussain, Omar; Jahangoshai Rezaee, Mustafa; GhanbarTehrani, Nasim
ABSTRACT: Easing transport congestion within a crowded urban environment requires management of travel demand. Managing traffic congestion in urban areas requires a set of effective policies and knowing when to apply them. In this paper, we focus on the managers' need to determine the most effective policies to respond to changing travel demands. We propose a new framework to achieve this aim by applying a combination of a System Dynamics approach and a Data Envelopment Analysis technique. Despite previous studies that integrate discrete-event simulation with multi-criteria decision-making approaches, the combination of a system dynamics approach with a data envelopment analysis technique proposed in this paper shows an improvement both in forecasting the travel demand and managing it through effective policies.